Change now! : five steps to better leadership - Scisco, Peter (Center for Creative Leadership, 2014)
Make Changes For Yourself. For Others. For The Future. What brought you to where you are now probably won't take you to where you want to go. If you want to reach the next level of performance or leadership, now is the time to DEVELOP, the time to GROW. Now is the time to CHANGE. The FIVE STEPS in this book will help you achieve the changes you seek. You will identify where to focus your development energy. You will create goals that work for you. You will craft a plan for achieving your goals. You will learn how to anticipate and overcome obstacles. And you'll figure out how to stay on course.